2016
DOI: 10.18632/oncotarget.6913
|View full text |Cite
|
Sign up to set email alerts
|

Alpha-fetoprotein still is a valuable diagnostic and prognosis predicting biomarker in hepatitis B virus infection-related hepatocellular carcinoma

Abstract: Use of serum alpha-fetoprotein (AFP) in clinical practices has been challenged in recent years, due to the lack of specificity and sensitivity. Here we conducted a retrospective study to evaluate the diagnostic and prognostic value of serum AFP among hepatocellular carcinoma (HCC) patients with their pathogenic features taken into consideration. The cohort for this study comprised 318 cases of hepatitis and 731 cases of cirrhosis, as well as 796 HCC patients. Using 11.62ng/mL as a cut-off value, the positive r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
27
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(33 citation statements)
references
References 12 publications
4
27
1
1
Order By: Relevance
“…AFP is a useful diagnostic marker for HCC, and roughly 50%-70% of adults with HCC have increased levels of AFP. 23,24 In this study, AFP was found to be related to HCC progression from stage A to stage D and was basically positively correlated, which suggests that higher serum levels of AFP were more likely to present with advanced stage HCC with severe liver dysfunction and compromised performance status. γ-GT mainly exists in liver cell membrane and microsome.…”
Section: Discussionmentioning
confidence: 56%
“…AFP is a useful diagnostic marker for HCC, and roughly 50%-70% of adults with HCC have increased levels of AFP. 23,24 In this study, AFP was found to be related to HCC progression from stage A to stage D and was basically positively correlated, which suggests that higher serum levels of AFP were more likely to present with advanced stage HCC with severe liver dysfunction and compromised performance status. γ-GT mainly exists in liver cell membrane and microsome.…”
Section: Discussionmentioning
confidence: 56%
“…In order to improve patients’ prognosis and long-term survival, early diagnosis of HCC is essential to implement curative interventions [5]. Alpha-fetoprotein (AFP) is the most commonly used serological biomarker for HCC [6, 7]. However, the clinical diagnostic accuracy of AFP is unsatisfactory due to low sensitivity and specificity, and is no more recommended by European Association for the Study of the Liver (EASL) [8, 9].…”
Section: Introductionmentioning
confidence: 99%
“…In China, AFP is the only serum biomarker included in the diagnostic criteria for HCC, whereas other countries suggest the use of a combination of non-invasive biomarkers for surveillance in high-risk populations. At present, AFP is the most effective diagnostic indicator for HCC (36). A recent meta-analysis of the diagnostic value of AFP in HCC determined a pooled sensitivity of 66%, a specificity of 86% and an AUC value of 0.87 (37).…”
Section: Discussionmentioning
confidence: 99%